An analysis of the use of basic falling and rising tunes in some interviews from The Ellen Show - Lê, Thị Minh Nguyệt (University of Languages and International Studies, 2017)
How to speak English with the appropriate intonation? How to teach and learn English intonation effectively and properly? etc. They are always big questions under restless mind of English teachers and learners not only in Viet Nam but also in the English-s (...)